Allelic Loss of 14q and 22q, NF2 Mutation, and Genetic Instability Occur Independently of c-kit Mutation in Gastrointestinal Stromal Tumor - Fukasawa, Tomoki; Chong, Ja‐Mun; Sakurai, Shinji; Koshiishi, Naoki; Ikeno, Rie; Tanaka, Akira; Matsumoto, Yoshiro; Hayashi, Yukiko; Koike, Morio; Fukayama, Masashi (Cancer science, 2000)
Gastrointestinal stromal tumor (GIST) is the most common mesenchymal tumor of the gastrointestinal tract. Since c‐kit mutation occurs only in one‐third of GIST, there might be other molecular mechanisms. Loss of heterozygosity (LOH), microsatellite instability (MSI) and NF2 gene mutation were investigated in 22 GISTs (9 low‐risk and 13 high‐risk tumors). LOH and MSI were evaluated using 41 markers on 21 chromosomal arms, and NF2 gene mutation was examined by PCR‐SSCP. High frequency of LOH was observed on 14q (9/19, 47%), and 22q (17/22, 77%). The frequencies were similar in low‐risk and high‐risk tumors, and were unrelated with gastric or intestinal origin. Two other abnormalities, additional LOH on other chromosomes and MSI at more than two loci, were characteristic of the high‐risk tumors (P < 0.05). NF2 gene mutation was identified in two cases showing 22q‐LOH (8 bp deletion on the splice donor site of exon 7, and 1 bp insertion at position 432 of exon 4, which resulted in nonsense mutation). There was no significant correlation between these results and c‐kit gene mutation, which was observed in 8 of 22 tumors. Suppressor genes on 14q and 22q may be involved, independently of c‐kit gene mutation, in the development of GIST. NF2 contributes as a tumor suppressor in a small subset of GIST. These abnormalities are presumably followed by increased genetic instability.